University research legitimate social. A view from history (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2010)
The essay below is main purpose was to analyze the construct of social legitimacy of university research, from studying the historical aspects that define university research in Latin American scene. This task allowed to derive the conclusion that the meaning of social legitimacy of university research is related to the building of an institutional system that operationally linking science and technology with society as a whole and, synchronously, design mechanisms and processes that consolidate their dignity society as a source of knowledge and confidence in their products. Institutional system that allows conceiving the research process as a social construct that emerges from the university spatialtemporal context and is conditioned by the sociopsychological circumstances that surround and a concept of order, understood as disciplined and methodical process built from a system of beliefs and epistemological and methodological beliefs, shared and accepted by the entire university community in which research is part of that process, also framed in a referential system of knowledge, scientifically validated and able to transcend the particularity to integrate investigative networks that allows a diachronic sequence form a path of development through successive connections.
Keywords: university research; social legitimacy of university research; historical development of latin american thought on science and technology policies